2008
DOI: 10.1038/leu.2008.9
|View full text |Cite
|
Sign up to set email alerts
|

A novel histone deacetylase 8 (HDAC8)-specific inhibitor PCI-34051 induces apoptosis in T-cell lymphomas

Abstract: We have developed a potent, histone deacetylase 8 (HDAC8)-specific inhibitor PCI-34051 with 4200-fold selectivity over the other HDAC isoforms. PCI-34051 induces caspase-dependent apoptosis in cell lines derived from T-cell lymphomas or leukemias, but not in other hematopoietic or solid tumor lines. Unlike broad-spectrum HDAC inhibitors, PCI-34051 does not cause detectable histone or tubulin acetylation. Cells defective in T-cell receptor signaling were still sensitive to PCI-34051-induced apoptosis, whereas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
365
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(387 citation statements)
references
References 50 publications
10
365
0
2
Order By: Relevance
“…We compared the specificity of the active and inactive HDAC inhibitors (Table S2). Although the majority of the inhibitors in our set have known activity against multiple HDAC proteins, making it difficult to identify the specific HDAC target, inhibitors selective for HDAC6 (Tubastatin) (28) and HDAC8 (PCI-34051) (29) did not score in our screen, making it unlikely that either of these HDAC proteins is involved in maintaining aberrant chromatin accessibility in Ewing sarcoma. The overall reproducibility of the screen confirms the robustness of HT-FAIRE as an approach for discovering biologically relevant compounds using a small, focused compound library.…”
Section: Resultsmentioning
confidence: 96%
“…We compared the specificity of the active and inactive HDAC inhibitors (Table S2). Although the majority of the inhibitors in our set have known activity against multiple HDAC proteins, making it difficult to identify the specific HDAC target, inhibitors selective for HDAC6 (Tubastatin) (28) and HDAC8 (PCI-34051) (29) did not score in our screen, making it unlikely that either of these HDAC proteins is involved in maintaining aberrant chromatin accessibility in Ewing sarcoma. The overall reproducibility of the screen confirms the robustness of HT-FAIRE as an approach for discovering biologically relevant compounds using a small, focused compound library.…”
Section: Resultsmentioning
confidence: 96%
“…Inhibition of meiotic histone deacetylation has been found to induce aneuploidy in fertilized mouse oocytes, which resulted in embryonic death in utero at an early stage of development (Akiyama et al 2006). Furthermore, it has been shown that treatment with inhibitors of histone deacetylase induced apoptosis of cancer cells and some of such inhibitors have been used as anticancer agents (Cheong et al 2003, Maggio et al 2004, Balasubramanian et al 2008. In summary, it is possible that pyruvate prevents oocyte aging by providing energy for oocyte metabolism and by inhibiting apoptosis.…”
Section: N Liu Y-g Wu and Othersmentioning
confidence: 99%
“…Letter HDAC1 IC 50 = 4 μM), 15 which is a tool molecule most often utilized to study the effects of HDAC8 inhibition.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%